2010
DOI: 10.1093/carcin/bgq234
|View full text |Cite|
|
Sign up to set email alerts
|

Retracted: 2-Tellurium-bridged β-cyclodextrin, a thioredoxin reductase inhibitor, sensitizes human breast cancer cells to TRAIL-induced apoptosis through DR5 induction and NF-κB suppression

Abstract: Tumor necrosis factor-related apoptosis-inducing ligand (TRAIL) exhibits potent antitumor activity via membrane receptors on cancer cells without deleterious side effects for normal tissue. Unfortunately, breast cancer cells, as many other cancer types, develop resistance to TRAIL; therefore, TRAIL sensitizing agents are currently being explored. 2-Tellurium-bridged β-cyclodextrin (2-TeCD) is a synthetic organotellurium compound, with both glutathione peroxidase-like catalytic ability and thioredoxin reductase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
26
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 44 publications
0
26
0
Order By: Relevance
“…However, we do not provide mechanistic evidence that how this effect achieved and how this effect could be correlated with the TrxR inhibitory activity [28]. In this study, we have examined whether DTCD (a novel synthetic TrxR inhibitor) and TRAIL interact to enhance their cytotoxicity towards ovarian carcinoma cells with the previous results, the present study show that DTCD could also potentiate TRAIL-triggered apoptosis through DR5 up-regulation.…”
Section: Discussionmentioning
confidence: 69%
“…However, we do not provide mechanistic evidence that how this effect achieved and how this effect could be correlated with the TrxR inhibitory activity [28]. In this study, we have examined whether DTCD (a novel synthetic TrxR inhibitor) and TRAIL interact to enhance their cytotoxicity towards ovarian carcinoma cells with the previous results, the present study show that DTCD could also potentiate TRAIL-triggered apoptosis through DR5 up-regulation.…”
Section: Discussionmentioning
confidence: 69%
“…Regarding miR-149C>T, it is a proapoptotic miRNA to repress the expression of Akt1 and E2F1. Silencing of Akt1 and E2F1 can induce apoptosis in human tumor cell lines (Lin et al, 2010(Lin et al, , 2011. Previous studies showed that polymorphism in miR-149C>T can change the expression of mature miRNAs or the binding activities to target mRNA, and thus influence cancer risk through various mechanisms (Lin et al, 2010(Lin et al, , 2011.…”
Section: Discussionmentioning
confidence: 99%
“…Silencing of Akt1 and E2F1 can induce apoptosis in human tumor cell lines (Lin et al, 2010(Lin et al, , 2011. Previous studies showed that polymorphism in miR-149C>T can change the expression of mature miRNAs or the binding activities to target mRNA, and thus influence cancer risk through various mechanisms (Lin et al, 2010(Lin et al, , 2011. Previous studies reported that the association between polymorphism in miR-149C>T and risk of various cancers, such as breast cancer, lung cancer, head and neck cancer, colorectal cancer and HCC, but the results are inconsistent (Hu et al, 2009;Liu et al, 2010;Vinci et al, 2011;Kim et al, 2012;Du et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Organotellurium compounds, which are similar to organoselenium compounds, have been employed as glutathione peroxidase mimics [35][36][37] and described to be promising biomaterials as pharmacological agents for antioxidant and anticarcinogen therapeutics 38,39 . There have been some studies on organotellurium compounds in our group, including coordination responsive telluride-containing polymers 40 and layer by layer films 41 , which can both release cis-platinum in the presence of multi-amine containing molecules (e.g.…”
Section: Introductionmentioning
confidence: 99%